Lexical Bundles in Chemistry Research Articles - Zare, Javad; Valipouri, Leila (Frontiers in Psychology, 2022)
The purpose of this corpus-based study was to investigate whether different sections in chemistry research articles, i.e., abstract, introduction, and results & discussion, rely on different sets of lexical bundles. Lexical bundles, associated with the above sections, were extracted from a corpus of 4 million words comprising 1,185 chemistry research articles, using WordSmith Tools 5.0, and were categorized according to their functions. Altogether, 197 key bundles were identified in the three sections of chemistry research articles, 15 in abstract, 99 in introduction, and 83 in the results & discussion section. Two functions also emerged for lexical bundles in chemistry research articles, including purpose-oriented bundles which refer to the aim/aims of the study; and literature-oriented bundles which are used to refer to the literature. Altogether, the results showed that various sections in chemistry RAs are associated with specific sets of lexical bundles and as such deal with different rhetorical functions.